1998
DOI: 10.1097/00006534-199811000-00044
|View full text |Cite
|
Sign up to set email alerts
|

Successful Reconstruction of Refractory Posttraumatic Skull Base Defects with the Free Radial Forearm Flap

Abstract: After our experience with two patients who had persistent posttraumatic defects of the anterior skull base, we recommend using a deepithelialized free radial forearm flap for one-stage reconstruction. The flap provides a thin, water-tight barrier between the cranial cavity and the subcranial spaces for effective prevention of cerebrospinal fluid leakage and ascending infection. It is particularly useful when local flap options are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Traumatic facial nerve palsy is a common cause of facial paralysis that the clinician is likely to encounter 1 . In a large series reported by May, 17% of patients with facial paralysis had trauma as the cause 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic facial nerve palsy is a common cause of facial paralysis that the clinician is likely to encounter 1 . In a large series reported by May, 17% of patients with facial paralysis had trauma as the cause 2 .…”
Section: Discussionmentioning
confidence: 99%
“…6 The RFFF can be used in anterior and lateral skull base reconstructions with good results. 6 Lorenzini et al 7 have reported the use of RFFF to reconstruct refractory post-traumatic anterior skull base defects. One of their patients had recurrent meningitis from an ethmoidal encephalocele, and the other had a persistent CSF leak after a gunshot wound.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The pericranial flap is most commonly used for primary repair; use of skin, galeal, and various free muscle flaps has been described in patients who do not have sufficient native tissue. 3,6,7 To provide more rigid fixation, some authors have also reported using bone grafts and metallic mesh in conjunction with soft-tissue repair. Because of the higher risk of postoperative infections, however, the application of avascular tissue has not become popular.…”
mentioning
confidence: 99%